Written Corrective Feedback and Its Effects on English Department Students’ Writing Drafts - Febitya A Adisca; Josefa J Mardijono (Kata Kita: Journal of Language, Literature, and Teaching, 2014)
This thesis investigates the teacher’s Written Corrective Feedback (WCF) strategies used in the students’ writing drafts and the effects analyzed from the comparison between the first and final drafts. It consists of fifty eight students’ writing drafts as the source of data limited to language use (LU) and vocabulary. The theories applied were the WCF strategies by Ellis (2009a); the effects of written feedback to students by Hyland (2003), and supported by Ferris (2006). The qualitative approach was used in this study. The finding revealed that the strategies used in the class were Direct CF (430 times), and Indirect CF (329 times). The effects were Error corrected, Incorrect change, No change, and Deleted text. Moreover, it was revealed that LU problem was more noticed by the students to be corrected. In conclusion, WCF can guide the students to be more aware of their mistakes and to improve their writing.